THEORETICAL APPROACHES TO THE CONCEPT OF FIELD IN LINGUISTICS (Scientific journal of the Fergana State University, 2024)
In linguistics, the concept of field has been attracting interest and being studied by scientists for several years. In fact, this term, which appeared in physics, also entered linguistics. A group of words with a common lexical meaning is considered a field. However, different scientists approached field theory in different ways. This article provides detailed information about the importance of the field and the semantic field in linguistics, as well as the theoretical opinions given to this concept by scientists. The concept of semantic field is of great importance in linguistics. The concept of semantic field was first used by the German scientist J.Trier in his articles and works, and the scientist emphasizes that each word belongs to a certain field. In addition, it can be said that the scientist mentioned the term semantic field as "concept field" in his works. According to him, all words in existence belong to a certain semantic field. Field theory, which appeared in world linguistics, especially in German linguistics, later entered Uzbek linguistics. In the 90s of the last century, the study of the semantic field theory entered Uzbek linguistics on a large scale. After that, words began to be attached to a certain field.